Ionic-liquid-based aqueous biphasic systems as concentration and purification platforms of cancer biomarkers - Pereira, Matheus Mendonça (2017)
Cancer is worldwide a major cause of death, with ca. 14 million new diagnosed cases each year. Therefore, the search for more efficient early-stage diagnosis methods is crucial aiming at increasing the treatment rate and survival of patients, as well as to decrease the expenses associated to advanced treatment. Prostate specific antigen (PSA) and lactate dehydrogenase (LDH) are proteins commonly found in human fluids (urine and serum), and have been considered as cancer biomarkers and in the monitoring of cancer treatment. However, due to their low concentration and the complexity of biological matrices with a large amount of other metabolites present (proteins, DNA, RNA), the pretreatment of samples for their concentration and purification is usually applied. In this work, alternative pretreatment techniques based on aqueous biphasic systems (ABS) composed of ionic liquids (ILs) have been studied to extract, concentrate and purify proteins that can be used as cancer biomarkers, such as PSA and LDH. To this end, several preliminary works were performed to identify the most promising phase-forming components and conditions to create ABS that could be used for the extraction of proteins. These works comprise studies on the extraction of amino acids and model proteins in ABS, followed by investigations on their use with more complex matrices. Finally, ABS were investigated for the extraction and concentration of tumor biomarkers, namely PSA and LDH. In summary, the versatility of ILs allows the tailoring of the ABS extraction and concentration capacity, selectivity, and/or induced precipitation of cancer biomarkers from human fluids. The systems here developed are a viable and efficient alternative for the pretreatment of biological samples (serum and urine), thus contributing to the development of early-stage methods of cancer diagnosis.